Care providers’ views on burden of psychosomatic symptoms of IS-traumatized female refugees participating in a Humanitarian Admission Program in Germany: a qualitative analysis - Rometsch, Caroline; Denkinger, Jana Katharina; Engelhardt, Martha; Windthorst, Petra; Graf, Johanna; Nikendei, Christoph; Zipfel, Stephan; Junne, Florian (PLOS ONE, 2020)
Background Traumatized refugees often suffer from diverse psychosomatic symptoms. Female Yazidi refugees from Northern Iraq who survived attacks of the so-called “Islamic State” were brought to Germany to receive special medical and psychotherapeutic treatment in a unique worldwide humanitarian admission program (HAP). Here, we report on their psychosomatic symptoms and helpful strategies from the perspective of care providers. Methods Care providers (N = 84) in this HAP were interviewed in an individual setting as well as in focus groups to gather information about the HAP beneficiaries’ psychosomatic symptoms. Data analysis followed Qualitative Content Analysis by Mayring. Results The care providers reported five main psychological burdens of the Yazidis: 1) insecurity regarding loss, 2) worries about family members, 3) ambivalence about staying in Germany or returning to Iraq, 4) life between two worlds and 5) re-actualization of the traumatic experiences. The predominant psychological symptoms the care providers noticed were fear, depressive symptoms, feelings of guilt, and sleep and eating disorders. Regarding somatic symptoms, the care providers mainly received complaints about pain in the head, back, chest and stomach. Helpful strategies for providing adequate health care were care providers’ cooperating with physicians, precise documentation of beneficiaries’ symptoms, and additional support in directing the beneficiaries through the health care system. Regarding psychotherapy, interpreters help to overcome language barriers, onsite psychotherapy, flexible therapy appointments, psychoeducational methods, time for stabilization, and support in coping with daily life aspects. In the care providers’ experience, psychotherapists have to build a relationship of trust. After grief therapy, a trauma-specific therapy in a culturally adapted way is possible. Conclusion The HAP is a unique model health care program to offer highly traumatized refugees medical and psychological help. Care providers reported on several (psycho-)somatic symptoms of the traumatized women. The strategies the HAP care providers perceived as helpful can be recommended for similar projects in the future.
Gesehen am 23.11.2020